2021
DOI: 10.3390/cancers14010019
|View full text |Cite
|
Sign up to set email alerts
|

GPR87 Promotes Metastasis through the AKT-eNOS-NO Axis in Lung Adenocarcinoma

Abstract: Lung adenocarcinoma is one of the leading causes of cancer-related deaths. Despite the availability of advanced anticancer drugs for lung cancer treatment, the prognosis of patients still remains poor. There is a need to explore novel oncogenic mechanisms to overcome these therapeutic limitations. The functional experiments in vitro and in vivo were performed to evaluate the role of GPR87 expression on lung adenocarcinoma metastasis. The public lung adenocarcinoma TCGA dataset was used to determine the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…GPR87 (G protein-coupled receptor 87) is one of the GPCR family and is in the chromosome 3q24 [41]. Recent studies have con rmed that GPR87 is overexpressed in several malignancies such as pancreatic cancer [42], lung cancer [43] and bladder cancer [44]. Bai's research proved that GPR87 might participate in tumorigenesis and progression of lung cancer, which may also be related to immune in ltration [45].One study detected that GPR87, as an oncogene, is expressed in pancreatic cancer cells and promotes cancer proliferation and metastasis by driving the NF-κB signaling pathway [42].…”
Section: Discussionmentioning
confidence: 99%
“…GPR87 (G protein-coupled receptor 87) is one of the GPCR family and is in the chromosome 3q24 [41]. Recent studies have con rmed that GPR87 is overexpressed in several malignancies such as pancreatic cancer [42], lung cancer [43] and bladder cancer [44]. Bai's research proved that GPR87 might participate in tumorigenesis and progression of lung cancer, which may also be related to immune in ltration [45].One study detected that GPR87, as an oncogene, is expressed in pancreatic cancer cells and promotes cancer proliferation and metastasis by driving the NF-κB signaling pathway [42].…”
Section: Discussionmentioning
confidence: 99%
“…The G proteincoupled receptor GPR87 is overexpressed in a variety of cancers, and studies have reported that GPR87 plays a key role in the proliferation of lung cancer cells, and indicated its potential as a new target for lung cancer therapy (51)(52)(53). GPR87 overexpression promotes EMT, significantly reduces the expression of the epithelial marker E-cadherin and increases the expression of the mesenchymal cell marker N-cadherin, and enhances the invasive and metastatic phenotype of cancer cells, which is associated with poor patient prognosis (54). TUBA4B can act as a tumor suppressor in various cancers (55,56), and low expression of TUBA4B is a predictor of poor prognosis and regulated cell proliferation in non-small cell lung cancer (57).…”
Section: Discussionmentioning
confidence: 99%